2019
DOI: 10.1371/journal.pone.0214643
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring stages: A study of undergraduate mentoring in palliative medicine in Singapore

Abstract: Background Mentoring nurtures a mentee’s personal and professional development. Yet conflation of mentoring approaches and a failure to contend with mentoring’s nature makes it difficult to study mentoring processes and relationships. This study aims to understand of mentee experiences in the Palliative Medicine Initiative (PMI). The PMI uses a consistent mentoring approach amongst a homogeneous mentee population offers a unique opportunity to circumnavigate conflation of practices and the limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 70 publications
2
42
0
Order By: Relevance
“…A newer perspective however sees the development of mentoring relationships occur in stages. To create a stable, effective and nurturing environment, Krishna et al 17 posit clear mentoring stages in the form of recruitment; aligning of expectations; the matching process; pre-mentoring meetings and training processes; and the subsequent mentoring relationship. For more targeted support and efficacious mentoring outcomes, it was suggested that each stage contain specific competencies to be met by the mentees in order for the mentoring relationship to advance.…”
Section: Journal Of Medical Education and Curricular Developmentmentioning
confidence: 99%
“…A newer perspective however sees the development of mentoring relationships occur in stages. To create a stable, effective and nurturing environment, Krishna et al 17 posit clear mentoring stages in the form of recruitment; aligning of expectations; the matching process; pre-mentoring meetings and training processes; and the subsequent mentoring relationship. For more targeted support and efficacious mentoring outcomes, it was suggested that each stage contain specific competencies to be met by the mentees in order for the mentoring relationship to advance.…”
Section: Journal Of Medical Education and Curricular Developmentmentioning
confidence: 99%
“…However, some of the review team believed that the decision to adopt directed content analysis to evaluate the data based on Miller's Pyramid (36)(37)(38) required further evidencing. As a result, 2 members of the study team carried out independent analyses of the data using a directed content analysis approach (41,42). The 2 members of the study team discussed their findings online and at face-to-face meetings and employed a "negotiated consensual validation" approach to determine final list of themes (43)(44)(45).…”
Section: Stage 4: Data Characterization and Analysismentioning
confidence: 99%
“…Mentoring nurtures professional and personal development [1], improves learning and clinical competency and enhances career satisfaction amongst mentees and mentors [2,3]. These successes are largely reliant upon the mentor's ability to nurture personalized mentoring relationships and steer the mentoring process [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. To do so, mentors adopt many supportive and educational roles [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%